Age structure of cohorts of mosquitoes from the field using shortwave infrared spectroscopy before and after ULV adulticide treatment - Christopher L. Swab; Barry W. Alto; Georgette Kluiters; Frank H. Cornine; Sam R. Telford (Parasites & Vectors)
Abstract Background The timely assessment of mosquito control efficacy through monitoring the age structure of wild cohorts of adult mosquitoes would improve operational decision making by control personnel. Analysis of shortwave infrared cuticular spectra for cohorts of laboratory reared Anopheles gambiae and Aedes aegypti of known age has shown that spectra outlier fraction is higher for cohorts of younger versus older weighted average age. This study investigates differences in outlier fraction of shortwave infrared cuticular spectra from wild cohorts of host-seeking mosquitoes of different species collected pre- and postultra-low volume (ULV) adulticiding (pyrethroid derivative, Etofenprox), with the hypothesis that post-treatment cohort spectra will have a higher outlier fraction than pretreatment due to younger mosquitoes replacing older ones killed by treatment. Methods Over 15,000 mosquitoes representing eleven species were collected 1 day pre-ULV adulticide application and 2 days post application during four biweekly treatments conducted at a site near Westford, Massachusetts from July to August of 2023. Shortwave infrared absorbance measurements were taken on 3100 specimens apportioned from all treatments and collection days, and spectra were then aggregated to pre- and post-treatment datasets for each species. Results Measurable changes occurred in pre- versus post-treatment cohort spectra outlier fraction for all species. A total of 8 of 11 species showed an increase in outlier fraction for post-treatment cohorts when aggregated over a 2-day post-treatment period, indicating replacement of older by younger mosquitoes. Analysis of abundance versus spectra outlier fraction over pre- and post-treatment collection days showed varying trends by species, implying an impact from recruitment of adults from new cohorts during the post-treatment period. Conclusions We believe the technique shows promise for monitoring the age-structure of wild cohorts of mosquitoes over time. The method is particularly suitable for surveillance programs since it is rapid, incorporates economic equipment, involves only minimal training, does not require freshly killed mosquitoes and does not use machine learning. Future research should comprise longer post-treatment periods for better trend analysis and be directed toward geographically distinct and problematic mosquito vectors of importance. Further refinements in assessing the utility of the outlier fraction technique for age-grading may consider the influence of mosquito diet and infection with pathogens and focus on potential impacts from mosquito diet and parasitism. Graphical abstract